Analysing art and artworks: introducing new theoretical frameworks to address the problem of art appreciation and criticism in universities/colleges. Issue 1 (2nd January 2022) - Akpang, Clement Emeka
Abstract: Writing about art is a complex task that differs considerably from other forms of writing because it requires detailed understanding and application of certain theoretical frameworks for visual analysis. This has proven to be a major challenge amongst university and college students in Nigeria who grapple with interpreting visuals into text. The objective of this research is to identify the factors that impede students' writing abilities in art departments through literature review, then develop a conceptual guide to art appreciation and criticism for undergraduates and budding art critics. The research demonstrates that emphasis on the aesthetic philosophy of art and the predominant creative pedagogy used for art tutelage in Nigeria is responsible for the poor approach to art writing amongst students. To address this problem, a combination of three theoretical frameworks: Ekphrasis, Formal Analysis and Iconographic Analysis are used to develop a new five-step-system for art appreciation. Results show that the juxtaposition of analytical elements from Ekphrasis, Formal and Iconographic Analysis leads to the development of a simple but effective theoretical framework for writing about art which covers five key areas of description, analysis, context, meaning and judgement. Having tested this new framework with tremendous success, this research concludes that the application of this five-step-system will improve writing about art in tertiary institutions by acquainting students with the theoretical tools/lexicons to effectively analyse their own works and those of established artists.